Analisa Penjatuhan Sanksi Administrasi Dan Sanksi Pidana Dalam Penanganan Tindak Pidana Perbankan Ditinjau Dari Undang-Undang Nomor 21 Tahun 2011 Tentang Otoritas Jasa Keuangan Dan Undang-Undang Nomor 7 Tahun 1992 Tentang Perbankan Beserta Perubahannya - Pinandita, Satria Anggara (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Criminal acts, crimes, and law violations continue to evolving along with the development of technology and economic growth. Which also results in the arising of crime in the banking sector. In the prevailing laws and regulations, Crime in the Banking Sector may be subject to criminal and administrative sanctioning. Criminal sanctions and administrative sanctions against Crimes in Banking are regulated in Law Number 21 of 2011 concerning the Financial Services Authority and Law Number 7 of 1992 concerning Banking. In the imposition of criminal sanctions and administrative sanctions, individuals and Financial Services Institutions in the Banking Sector can be imposed.